(untitled) (Global Journal of Human-Social Science, 2019)
The Lake Kinneret and its Drainage Basin ecosystems have undergone significant changes. Those ecosystem modifications include Anthropogenic and Natural processes. A comprehensive overview of data collected during 1970-2018 about relations between Lake Kinneret and its drainage basin is summarized in this paper. The data evaluation is aimed at the discovery of the dominant factors which has an impact on nutrient inputs into Lake Kinneret. The nutrient sources in the Hula Valley and their water-mediated migration towards Lake Kinneret as runoff and through subterranean preferential channels is discussed. It is suggested that the dominant mechanism of nutrient export from the Hula Valley to Lake Kinneret is mostly discharge-dependent. The long-term decline of Organic Nitrogen and Total Dissolved Phosphorus is due to Fishponds reduction and sewage removal. The nitrate migration is, therefore, precipitation capacity-dependent and significantly reduced during drought periods.